Intersecting and Recognizing The Value of Culture Through Local History Drama “Topekkong Agreement” - Syukri, Muhammad; Bahrun, St. Rahmaniah (JLE: Journal of Literate of English Education Study Program, 2021)
Presenting drama as a tool in the learning process, especially English learning has been advanced. For a local history drama technique, one of them is to use drama. In this study, to increase the students' knowledge of their community, a drama using local history is interesting. The drama will build up learners who are proud of their community. In this case, the analysis shows how students intersect and recognize the importance of culture. Via a questionnaire, I collected the data to understand the interest of students by using the local history drama in the learning process. The element that the study finds is how the students intersect and understand the culture's meaning. The outcome indicates that none of the students state a derogatory comment about the use of techniques for local history drama. Sixty-five (86.67 percent) students were highly involved in the students' range of 66-80 percent. The highest score was 79, categorized as highly interested, and the lowest score was 61, categorized as an interesting group, based on the student scores on the questionnaire (see appendix 6 ). It is proposed that learning English through the use of local history drama could present the understanding of their cultural value as a pride in their life to the students.